Quorum Sensing and Cyclic di-GMP Exert Control Over Motility of Vibrio fischeri KB2B1 - Dial, Courtney N.; Eichinger, Steven J.; Foxall, Randi; Corcoran, Christopher J.; Tischler, Alice H.; Bolz, Robert M.; Whistler, Cheryl A.; Visick, Karen L. (Frontiers in Microbiology, 2021)
Bacterial motility is critical for symbiotic colonization by Vibrio fischeri of its host, the squid Euprymna scolopes, facilitating movement from surface biofilms to spaces deep inside the symbiotic organ. While colonization has been studied traditionally using strain ES114, others, including KB2B1, can outcompete ES114 for colonization for a variety of reasons, including superior biofilm formation. We report here that KB2B1 also exhibits an unusual pattern of migration through a soft agar medium: whereas ES114 migrates rapidly and steadily, KB2B1 migrates slowly, then ceases migration. To better understand this phenomenon, we isolated and sequenced five motile KB2B1suppressor mutants. One harbored a mutation in the gene for the cAMP-receptor protein (CRP); because this strain also exhibited a growth defect, it was not characterized further. Two other suppressors contained mutations in the quorum sensing pathway that controls bacterial bioluminescence in response to cell density and two had mutations in the diguanylate cyclase gene VF_1200. Subsequent analysis indicated that (1) the quorum sensing mutations shifted KB2B1 to a perceived low cell density state and (2) the high cell density state inhibited migration via the downstream regulator LitR. Similar to the initial point mutations, deletion of the VF_1200 diguanylate cyclase gene increased migration. Consistent with the possibility that production of the second messenger c-di-GMP inhibited the motility of KB2B1, reporter-based measurements of c-di-GMP revealed that KB2B1 produced higher levels of c-di-GMP than ES114, and overproduction of a c-di-GMP phosphodiesterase promoted migration of KB2B1. Finally, we assessed the role of viscosity in controlling the quorum sensing pathway using polyvinylpyrrolidone and found that viscosity increased light production of KB2B1 but not ES114. Together, our data indicate that, while the two strains share regulators in common, they differ in the specifics of the regulatory control over downstream phenotypes such as motility.